Studying Ecosystem in Senior High School: The Utilization of CirGi Learning Model to Enhance Mastery of Biological Concepts - Lia Junita Harahap; Ratna Komala; Rizhal Hendi Ristanto (Indonesian Research Journal in Education |IRJE|, 2020)
Ecosystem concepts are not a science that is far from daily life. Therefore, teachers need an innovation that can support students’ mastery of the ecosystem concept. This study aims to analyze the influence of the CirGi (Cooperative Integrated Reading, Composition, and Guided Inquiry) learning model on the learners’ ecosystem concept mastery. This research uses a quasi-experiment method with a pre-post control group design with a sample of 104 students. Data collection is carried out using an instrument of ecosystem concept mastery in the form of multiple choices so that questions could cover all the materials. The data analysis technique used is an independent sample t-test. The conclusion of this study is that there is a significant influence of CirGi’s learning model on the learners’ mastery of ecosystem concept. The application of CirGi learning model on ecosystem material can revive reading activities along with environmental awareness.